A losing battle? Women`s sport pre- and post-COVID-19 - Bowes, A.; Lomax, L.; Piasecki, J. (European Sport Management Quarterly, 2021)
Research question: In 2019, women`s sport was reported as being on the rise. Increased participation rates, media coverage, investment and support were evident. Following the spread of COVID-19 across the globe, which halted most forms of competitive sport, there were repeated concerns about the future of women`s sport. This research aims to document elite sportswomen`s perceptions of the state of women`s sport pre-COVID-19 and the possible impact moving forwards. Research methods: Ninety five responses from an online, anonymous, qualitative questionnaire completed by elite sportswomen mainly based, in the UK, on the impact of COVID-19 on women`s sport were collected. Data were subject to a thematic analysis, to determine key concerns, and the frequency data of responses were quantitatively recorded. Results and findings: Most sportswomen felt that women`s sport was on an upward trajectory, but many juxtaposed that against inequality compared to men`s sport in terms of media coverage and finance. There were concerns that the subordinate position women`s sport, with less resources and support, will have severe implications post-COVID-19. However, there were considerations that a pause in sport would allow for personal development, increased participation upon sports return and space for a reconfiguration of sport. Implications: Those involved in sport are encouraged to think more critically about progress narratives in women`s sport. We caution that these hide perpetual, structural and symbolic inequalities and propose that they are positioned more coherently within wider gender equity agenda. This is a process that will require widespread cultural change.